2020
DOI: 10.3892/mco.2020.2002
|View full text |Cite
|
Sign up to set email alerts
|

A meta‑analysis of serological thymidine kinase 1 as a marker for colorectal benign and malignant tumor risk assessment

Abstract: The present study investigated whether a concentration of serum thymidine kinase 1 (STK1p) could be used to distinguish between healthy individuals, patients with colorectal benign tumors and individuals with colorectal cancer (CRC). The effectiveness of surgery on patients with CRC was monitored. A total of 20 publications containing patients with CRC (n=1,836), patients with colorectal benign tumors (n=774) and healthy controls (n=1,701) were analysed in the present meta-analysis. The publications were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
(43 reference statements)
2
9
0
Order By: Relevance
“…With an AUC score between 0.824-0.826, TK1 looked quite specific and could be projected as an independent marker for CRC diagnosis. Nevertheless, the joint detection of TK1+CEA + CA19-9 + CA72-4 offered a better diagnostic performance in the logistic regression model, which is consistent with some previous findings also (Liang et al, 2016;Ning et al, 2018;Yanfeng et al, 2018, Dang et al, 2020.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…With an AUC score between 0.824-0.826, TK1 looked quite specific and could be projected as an independent marker for CRC diagnosis. Nevertheless, the joint detection of TK1+CEA + CA19-9 + CA72-4 offered a better diagnostic performance in the logistic regression model, which is consistent with some previous findings also (Liang et al, 2016;Ning et al, 2018;Yanfeng et al, 2018, Dang et al, 2020.…”
Section: Resultssupporting
confidence: 91%
“…A meta-analysis revealed that serum TK1 significantly distinguished healthy persons and those with benign colorectal tumors from patients with CRC (p<0.000001). It also highlighted that benign tumor patients with serum TK1 values > 2.0 pmol/L had significantly higher chances of developing malignant colorectal tumors (Dang et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They concluded that the half-life of STK1c is a useful parameter for evaluating surgical response in lung cancer patients and that STK1c may be beneficial for early detection of disease. A separate meta-analysis performed by Dang et al studied whether serum TK1 protein levels (STK1p) measured using the ECL assay could distinguish between healthy patients (n = 1,701), benign colorectal tumors (n = 774), and colorectal cancer (CRC) (n = 1836) [ 125 ]. Twenty studies spanning from 2009 to 2019 were collected and evaluated.…”
Section: Tk1 Quantification Methods In Patient Seramentioning
confidence: 99%
“…Clinical evidence has supported that STK1p correlates significantly to tumor growth rates, clinical stages and evaluated for monitoring of tumor therapies and the prognosis of survival and relapse of various malignant tumors individually. Three network meta-analyses (NMAs) of lung (n = 2107) [ 17 ], colorectal (n = 1836) [ 18 ] and breast cancers (n = 1813) [ 19 ] conformed that the STK1p level increased significantly from normal to benign and then carcinomas (p < 0.0001). When the tumor was resected by extensive open surgery successfully, the level of STK1p decreased with a half-life of nearly 50%.…”
mentioning
confidence: 99%